Memantine-induced speech problems in two patients with autistic disorder - Alaghband-Rad, Javad (BioMed Central, 2013)
Stuttering is a complex speech disorder. There are two forms of stuttering: developmental stuttering and acquired stuttering. Developmental stuttering is a disorder of early childhood but acquired stuttering can develop at any age. Some medications can induce or deteriorate stuttering as an adverse effect. There are several reports of stuttering due to psychotropic drugs. Memantine, a glutamate antagonist used in the treatment of Alzheimer’s disease, has also been studied for the treatment of autism spectrum disorders. This report presents deterioration of stuttering and speech problem in two children with autistic disorder who were receiving memantine. Based on our knowledge, this is the first time these adverse drug reactions have been attributed to memantine. In conclusion clinicians should consider that speech problems including stuttering may be due to the consumption of memantine, especially, in children may be a side effect of memantine especially in children.